Staropruskie Enchiridion: Abrewiatura końcowego dyftongu - Smoczyński, Wojciech (Kalbotyra, 1997)
In the present article a survey is given of all instances of spellings of the types a) billē, weddē, semmē, b) billā, spigsnā, piencktā, c) widdewú. On the basis of this material the hypothesis is put forward that the macron is put over the final vowel sign as a mark of abbreviation, with standing for [-ei], for [-ai] and for [-ui]. Originally this had been a mark of the suspension of the nasal before a pause, e.g. = an. However, as soon as the tendency to change nasal diphthongs into oral diphthongs (-an > -ai etc.) got in, the vowel sign with a macron (-ā) became a means of marking a new type of diphthongs, such as [-ai]. Evidence of this can be found in the texts: spellings with and , and alternate in identical word forms as well as in forms belonging to the same morphological category (e.g., the 3-rd person present and preterite in -ei/-ai, and the nom. sing. f. in -ei/-ai or in -ui). On the assumption that the macron may be a marker of a diphthongal abbreviation, we can eliminate a number of contradictions arising from the traditional view of the macron over word-final -ē, -ā, -ū as a marker of stressed long vowels. More specifically, an explanation is provided 1) for the hitherto enigmatic exceptions from the Old Prussian sound law *ē > ī (semmē is against acc. sg. semmin), and 2) for the allegedly oxytonic forms of the 3-rd person present and preterite (billē, billā) and of the nom. sg. f. such as crixtisnā or semmē. An important consequence of accepting this hypothesis is that a more coherent picture of the oscillations in Old Prussian conjugation and declination can be gained.